Comparison of enrofloxacin and ceftiofur sodium for the treatment of relapse of undifferentiated fever/bovine respiratory disease in feedlot cattle - Abutarbush, Sameeh M. (Canadian Veterinary Medical Association, 2012)
This commercial field trial compared the efficacy of enrofloxacin and ceftiofur sodium in beef cattle at high risk of developing undifferentiated fever (UF), also known as bovine respiratory disease (BRD) that received tilmicosin at feedlot arrival, were diagnosed and initially treated for UF with tilmicosin, and subsequently required a second UF treatment (first relapse). Feedlot cattle (n = 463) were randomly assigned to 2 experimental groups: ENRO or CEF. Second UF relapse, 3rd UF relapse, overall case fatality and BRD case fatality rates were lower in the ENRO group than in the CEF group (P < 0.05). There were no differences in average daily gain (allocation to re-implant date), chronicity, histophilosis case fatality or miscellaneous case fatality rates between the groups (P ≥ 0.05). A per-animal economic advantage of Can$57.08 was calculated for the ENRO group versus the CEF group. In feedlot cattle in western Canada at high risk of developing UF, it was more cost effective to administer enrofloxacin than ceftiofur sodium for treatment of UF relapse.